Вопросы энергосбережения при совершенствовании электроприводов на судопропускных гидротехнических сооружениях - Парамонова, Валентина Ивановна; Скачков, Е. А. (НТУ "ХПИ", 2010)
The problem of energy saving on navigable sluices by means of controlled on frequency of the rotation of electro-hydraulic drives is considered. Their efficiency is shown. The structure of energy-saving electro hydraulic drive for devices of winches and locks is offered.
Power savings questions at perfection of electric drives on navigable hydrotechnical constructions
Keywords: ротор короткозамкнутый; привод электрогидравлический; затвор